PENGARUH PERSEPSI MAHASISWA TERHADAP MINAT BERTRANSAKSI DI BANK SYARIAH (Studi Kasus Mahasiswa Fakultas Agama Islam Universitas Muhammadiyah Bandung) - Erwanda, Alifianisa; Fikri, Yudistia Teguh Ali; Irawati (ASH-SHIDQU: JURNAL EKONOMI SYARIAH, 2025)
Perception is a view or assumption that arises from the information received. Perception plays an important role in understanding information or knowledge that affects a person's interest. Different perceptions in understanding the information or knowledge received can cause variations in interest. The purpose of this study is to ascertain how much perceptions based on knowledge and information affect students' desire in doing business with Islamic banks. Survey techniques used in this study, which is descriptive quantitative in nature, include questionnaires and interviews. One hundred students from Universitas Muhammadiyah Bandung made up the research sample. A questionnaire created utilizing a likert scale was used to collect data. Validity and reliability tests were performed on the instrument, and statistical tests, basic linear regression analysis, and traditional assumption tests were used to analyze the results. To facilitate calculations, Software for this investigation was SPSS version 25. The study's data analysis results indicate that, in the T test, perception (X) significantly influences interest in transacting with Islamic banks (Y), with a t count value more than the t table (11.048 > 1.660551), and 0.000 <0.10 is the significance value. The corrected R square, or coefficient of determination, is 0.555, or 55.5%, with other factors beyond the scope of the study influencing the remaining 44.5%..